EFFECT OF EARLY PATIENT ACTIVATION ON BONE MINERAL DENSITY DYNAMICS DURING OSTEOSYNTHESIS OF FEMORAL NECK FRACTURES - Salokhiddinov F.B (American Journals Publishing, 2024)
Objective: the effect of early activation of patients on the dynamics of bone mineral density during osteosynthesis of femoral neck fractures using an external fixation rod and wires.
Keywords: femoral neck fracture, bone mineral density, osteosynthesis, rod apparatus.